Examining the Effect of Teachers’ Occupational Alienation on Their Individual Job Performance (Journal of Management and Educational Sciences, 2025)
This study aimed to investigate the effect of teachers' occupational alienation on their individual job performance. The research was conducted with the relational screening model. According to the research results; it was revealed that the individual job performances of the teachers participating in the research were high and their perception of job alienation was low. In the examination according to gender; no difference was found in terms of job alienation between male and female teachers. In the examination according to marital status; no difference was found in terms of job alienation between married and single teachers. In the examination according to educational status; no difference was found in terms of job alienation between teachers with bachelor's and master's degrees. In the examination according to age; in the individual job performance dimension of the participants, the individual job performance perception of the 41 and over group was found to be higher than the 20-30 age group. In addition, in the general scale of job alienation of the participants, the job alienation perception of the 41-50 age group was found to be higher than the 20-30 and 51 and over groups. In the examination according to years of service; the individual job performance perception of teachers with 16 years of service and above was found to be higher than the teachers with 1-5 years of service. In the examination according to weekly working hours; the perception of individual job performance of teachers with weekly working hours between 26-50 hours was higher than teachers with weekly working hours between 15-25 hours. Finally, there was no significant relationship between the participants' individual job performance scores and their perceptions of total work alienation scores. It was also concluded that the participants' individual job performance scores did not significantly predict their work alienation perceptions.